Networked and integrated digital platforms for the university system - Davide Bruno; Felice D’Alessandro (Agathón)
The paper aims to stimulate and share new opinions on the opportunity to reorganise and enhance the wide universe of digital applications to handle the Italian university system, trying to outline a forward-looking scenario considered in its structural components (teaching, research and third mission) placing people at its core. The final aim is to design networked and integrated digital platforms in collaboration with CINECA Inter-University Consortium, with the aim to submit to it the areas of intervention where it is possible and desirable to think about the development and subsequent implementation of innovative and original products, making Italian universities catch up on the most qualified international situations by fostering the transition to an open, transparent, inclusive and sustainable system.